Respons Agronomi Tiga Varietas Ubi Kayu pada Berbagai Tingkat Kadar Air Tanah - . Suwarto; Eko Sulistyono; Giansar Prastowo (Jurnal Ilmu Pertanian Indonesia, 2018)
Cassava has been cultivated in almost the all region of Indonesia as a raw material of food, feed, and industries.  The productivity of cassava was varied among the region due to the variation of varieties used and growth environment, especially rainfall or water availability. Water deficit or drought stress will decrease the growth and yield of cassava.  Selecting tolerant variety to drought will be important to get high productivity. An experimental pot in the greenhouse has been conducted to know the growth and yield response to drought. Three varieties of cassava i.e Adira-1, Gajah, and Mangu were planted in the pot at three level of soil moisture content (SMC) 40-60, 60-80, and 80-100% of field capacity (FC). The cassava growth traits were influenced by SMC starting at 6 weeks after planting (WAP) for a number of leaves, at 8 WAP for stem girth, at 10 WAP for plant height, at 14 WAP for lobus width, and 15 WAP  for lobus length.  Root, stem, and leaves dry weight in the SMC of 40-60% FC were 64.4; 43.98, and 31.19% of the dry weight in 80-00% FC. Roots yield in the soil moisture content of 40-60% FC decreased by 76.2% and in the SMC of 40-60%, FC decreased by 38.4% compared to in the SMC of 80-100% FC. The water use efficiency and roots yield of Gajah variety were highest.